2020
DOI: 10.1021/acssuschemeng.0c02154
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Highly Stable Li–O2 Batteries with Full Discharge–Charge Capability: The Porous Binder- and Carbon-Free IrNi Nanosheet Cathode

Abstract: Rechargeable aprotic Li−O 2 batteries have drawn much attention in light of their ultrahigh theoretical energy density. However, the sluggish kinetics of oxygen cathode reactions lead to huge energy loss, while the unfavorable side reactions associated with the widely used carbon and binder account for fast battery decay during cycles. Herein, hierarchically holey IrNi alloy nanosheets are facilely designed on Ni foam substrate as a freestanding, binder-and carbon-free cathode to address these challenges. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Therefore, they concluded that Li 2 O 2 (or Li x O y , an intermediate of the Li 2 O 2 decomposition) can react with carbon electrodes at a high voltage and generate Li 2 CO 3 , which subsequently decomposes into CO 2 . Later, new carbon-free materials (e.g., IrNi) and modified carbon materials (e.g., ∼5 nm thick amorphous MoS 2 layer on CNT forest-covered graphite foam) were reported, but their stabilities under reactive oxygen species are limited. It was proved that IrO x and NiO x appeared in the cathode after 50 cycles and that Li 2 CO 3 accumulation was also found on the MoS 2 -modified cathode after 190 cycles.…”
Section: Parasitic Reactions Induced By Reactive Oxygen Speciesmentioning
confidence: 99%
“…Therefore, they concluded that Li 2 O 2 (or Li x O y , an intermediate of the Li 2 O 2 decomposition) can react with carbon electrodes at a high voltage and generate Li 2 CO 3 , which subsequently decomposes into CO 2 . Later, new carbon-free materials (e.g., IrNi) and modified carbon materials (e.g., ∼5 nm thick amorphous MoS 2 layer on CNT forest-covered graphite foam) were reported, but their stabilities under reactive oxygen species are limited. It was proved that IrO x and NiO x appeared in the cathode after 50 cycles and that Li 2 CO 3 accumulation was also found on the MoS 2 -modified cathode after 190 cycles.…”
Section: Parasitic Reactions Induced By Reactive Oxygen Speciesmentioning
confidence: 99%
“…However, recent studies have shown that carbon would react with the discharge products of Li 2 O 2 to form lithium carbonate and lithium acetate. These byproducts passivate the cathode surface and increase the overpotential, leading to the performance degradation of Li–O 2 batteries. This phenomenon stimulates the researcher to explore novel carbon-free cathode materials for high-performance Li–O 2 batteries. This has been well demonstrated in making two-dimensional conductive RuO 2 nanosheets as carbon-free catalysts with a reversible specific capacity of 900 mAh g –1 , exploring the TiC-based cathode with a specific capacity of around 350 mAh g –1 with stable cycling to 100 cycles and making the Magnéli phase Ti 4 O 7 with a capacity of about 350 mAh g –1 . However, these reported cathodes still suffer from low gravimetric capacity and limited cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…The known catalytic effect of cobalt has been introduced in Li-O 2 batteries as redox mediators [14,15], carbon-free cathodes [16,17] and carbon cathodes [18,19]. Among the latter, porous carbons with embedded cobalt and cobalt oxide nanoparticles have been widely investigated in the field of energy conversion and storage: lithium-ion batteries [20,21] lithium-sulfur batteries [22,23] and Li-O 2 batteries [24,25]; these last were mainly motivated by their ORR and OER catalytic activity [26].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%